Global trends and inequities in smoking-attributable aortic aneurysm burden from 1990 to 2021 with future projections - Zhang, Shuai; Hua, Zhaohui; Li, Zhen; Cao, Hui; Cheng, Shuai (Frontiers in Public Health, 2025)
IntroductionAortic aneurysm (AA) remains a critical global health challenge, with smoking identified as a major modifiable risk factor contributing to its morbidity and mortality. Despite advancements in screening and treatment, the absolute burden of AA has risen significantly, particularly in aging populations and regions with socioeconomic disparities. This study leverages data from the Global Burden of Disease Study to analyze trends in smoking-related AA burden from 1990 to 2021, focusing on mortality, disability-adjusted life years (DALYs), and socioeconomic determinants.MethodsUsing GBD 2021 data, we assessed age-standardized mortality rates (ASMR), age-standardized DALY rates (ASDR). Joinpoint regression identified trend inflection points, validated via grid search and Monte Carlo permutation tests, with annual percent change (APC) quantified. Age-period-cohort modeling was analyzed effects in populations aged ≥30 years (5-year age intervals). Decomposition analysis partitioned contributions of population growth, aging, and epidemiological factors. Spearman’s correlation linked the Sociodemographic Index (SDI) to AA burden. ARIMA modeling projected trends to 2022–2036.ResultsDespite a significant global decline in age-standardized mortality and DALYs, the absolute burden of smoking-related AA has increased, with marked disparities by sex, age, and socioeconomic development. Males consistently exhibited higher mortality and DALYs than females, and the older adults remained the most affected. Joinpoint regression and age-period-cohort modeling revealed declining trends in high-income regions but rising burdens in low-SDI areas. Decomposition analysis identified population growth and aging as key drivers of increased mortality and DALYs, while epidemiological improvements partially offset these trends. Socioeconomic analysis showed a threshold effect: AA burden increased with SDI up to a point, then declined with further development, suggesting effective health systems and tobacco control policies play a crucial role. Forecasts using ARIMA modeling predict a continued global decline in ASMR and ASDR by 2036, though disparities will persist, especially in low-resource settings.ConclusionThese findings underscore the need for targeted, equity-focused tobacco control and vascular health interventions to mitigate the evolving global impact of smoking-related AA.